Methods of exploiting agricultural real estate in the framework of reclamation In Algeria - Khelifi, Chaouki (Journal of Human Sciences, 2023)
The ownership and exploitation of agricultural real estate in Algeria has been subject of political, ideological, and even economic influences , especially in the transitional phase from the socialist system to the capitalist system, which resulted in the adoption of a reclamation as a pattern of ownership and/or exploitation of this type of real estate, the latter has taken many forms, in the beginning what is known as the possession of agricultural real estate ownership according to the law n° 83/18 of 13/08/1983 which we will address in a first time. However, after the change of the general trend in Algeria which appeared in the constitution of 1989; especially with regard to approved view of ownership and the attempt to liberalize the exploitation of property; including agricultural real estate, it was promulgated the national property law and the real estate orientation law; in 1990, which established a new pattern of agricultural land exploitation, and here the matter is related to agricultural concession that is transferable and not transferable into a cession, which we will discuss in the second time.